Takotsubo Cardiomyopathy : An Exploration of the Intersection Between Stress, Coronary Dysfunction, and Cardiac Outcomes - Rossi, Davide; Saraullo, Silvio; Magnano, Roberta; Pezzi, Laura; D’alleva, Alberto; Ricci, Fabrizio; Scollo, Claudio; Di Marino, Mario; Genovesi, Eugenio; Vitulli, Piergiusto; Forlani, Daniele; Renda, Giulia; et al. (Reviews in Cardiovascular Medicine, 2025)
Takotsubo syndrome (TTS) is an acute, reversible form of left ventricular dysfunction, typically triggered by emotional or physical stress. The hallmark feature is reversible regional wall motion abnormality extending beyond a single coronary distribution, most commonly presenting with an apical ballooning pattern. The pathophysiology is multifactorial, encompassing neurohormonal dysregulation, catecholamine-mediated toxicity, microvascular dysfunction, oxidative stress, inflammation, and metabolic disturbances. Nonetheless, despite growing recognition, an evidence gap persists in diagnosing TTS. Meanwhile, TTS is classified within myocardial infarction with non-obstructive coronary arteries (MINOCAs) and frequently treated as a diagnosis of exclusion. Further complicating the diagnostic algorithm, emerging evidence indicates that TTS and coronary artery disease (CAD) may coexist, suggesting a potential bidirectional relationship rather than a bystander phenomenon. Moreover, TTS shares several pathophysiological mechanisms with coronary microvascular dysfunction syndromes: angina with non-obstructive coronary arteries (ANOCAs) and ischemia with non-obstructive coronary arteries (INOCAs). These overlaps underscore the need for rigorous differential diagnosis and careful comprehensive evaluation of hemodynamic significance, plaque morphology, and microvascular phenotyping to enhance clinical recognition and optimize therapeutic decision-making. This review synthesizes current evidence on the diagnosis and management of TTS, emphasizing the intersection between TTS and coronary and microvascular disorders to promote a more targeted, mechanism-based therapeutic approach.
Keywords: cardiovascular imaging; coronary artery disease; microvascular dysfunction; neurohormonal dysregulation; stress cardiomyopathy; Takotsubo syndrome